Digital Literacy: Strengthening Gen Z's Character Based on Moderate Islam - Abdullah Khusairi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Digital transformation has shaped Gen Z's behavior in accessing information. Behind this pattern, they face serious challenges, including the rise of disinformation, misinformation, and malinformation, as well as the degradation of values due to harmful digital culture. This article aims to propose a paradigm of digital literacy based on moderate Islam for Generation Z, integrating critical awareness of information, digital ethics grounded in spiritual values, and the use of technology as a means of religious and character transformation in the digital age. This study employed a qualitative approach, incorporating literature review and analysis of digital literacy survey data. The findings reveal that Gen Z remains vulnerable to being trapped in echo chambers and filter bubbles due to low awareness of verification, confirmation, and comparison of information. Gen Z increasingly relies on social media as their primary source of academic information without adequate filtering mechanisms. This poses a risk to their well-being, necessitating strategies to strengthen digital literacy character as a defense against the negative impacts of digital transformation. This research proposes moderate Islam-based digital literacy as a new paradigm for Gen Z’s digital literacy, which includes Islamic Epistemic Vigilance, Critical awareness in filtering information to counter hoaxes, fake news, and hate speech. Islamic Ethical Digital, the internalization of internet ethics aligned with spiritual values that foster civilized digital behavior. Spiritual-Tech Integration, the use of digital technology as a means of spiritual transformation that is adaptive to the times. These findings emphasize that moderate Islam-based digital literacy strategy to empower Gen Z as agents of change